Exploring Students’ Willingness to Communicate (WTC) in STKIP Muhammadiyah Aceh Barat Daya - Nurul Amalia; Sukri Adani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Proficiency in English communication is an essential competency for university students. However, empirical research mapping Willingness to Communicate (WTC) across specific language skills within private universities in regional contexts remains scarce. This study investigates the WTC levels among students enrolled in the English Language Teaching program at STKIP Muhammadiyah Aceh Barat Daya, focusing on four dimensions: speaking, reading, writing, and comprehension. Employing a quantitative descriptive methodology, the study surveyed 50 students selected through total sampling. Data were gathered using a validated 27-item Likert-scale questionnaire (Cronbach’s Alpha = 0.956) and analyzed descriptively. Findings indicate that students' overall WTC is moderate, with average scores ranging from 2.98 to 3.24. Among the four dimensions, comprehension yielded the highest score (M = 3.24; SD = 0.596), suggesting greater psychological comfort in receptive communication activities. Speaking (M = 3.06; SD = 0.481) and reading (M = 3.06; SD = 0.528) both reflected moderate, balanced levels. In contrast, writing received the lowest score (M = 2.98; SD = 0.568), indicating heightened anxiety regarding grammatical accuracy and language conventions. These results underscore the necessity for educators and institutions to implement student-centered learning strategies that reduce psychological barriers and foster holistic student engagement.